Clinical application of superselective transarterial embolization of renal tumors in zero ischaemia robotic-assisted laparoscopic partial nephrectomy - Li, Haichang; Hu, Yuning; Lu, Dongning; Wang, Jingyun; Lin, Yanze; Zhong, Xugang; Mou, Yixuan; Yao, Cenchao; Wang, Zhida; Zhang, Xinyu; Wo, Qijun; Liu, Hanbo; et al. (Frontiers in Oncology, 2023)
To assess the feasibility and safety of zero ischaemia robotic-assisted laparoscopic partial nephrectomy (RALPN) after preoperative superselective transarterial embolization (STE) of T1 renal cancer. Methods: We retrospectively analysed the data of 32 patients who underwent zero ischaemia RALPN after STE and 140 patients who received standard robot-assisted laparoscopic partial nephrectomy (S-RALPN). In addition, we selected 35 patients treated with off-clamp RALPN (O-RALPN) from September 2017 to March 2022 for comparison. STE was performed by the same interventional practitioner, and zero ischaemia laparoscopic partial nephrectomy (LPN) was carried out by experienced surgeon 1-12 hours after STE. The intraoperative data and postoperative complications were recorded. The postoperative renal function, routine urine test, urinary Computed Tomography (CT), and preoperative and postoperative glomerular filtration rate (GFR) data were analysed. Results: All operations were completed successfully. There were no cases of conversion to opening and no deaths. The renal arterial trunk was not blocked. No blood transfusions were needed. The mean operation time was 91.5±34.28 minutes. The mean blood loss was 58.59±54.11 ml. No recurrence or metastasis occurred. Conclusions: For patients with renal tumours, STE of renal tumours in zero ischaemia RALPN can preserve more renal function, and it provides a safe and feasible surgical method.